Apple fruit superficial scald resistance mediated by ethylene inhibition is associated with diverse metabolic processes. (22nd December 2017) - Busatto, Nicola; Farneti, Brian; Commisso, Mauro; Bianconi, Martino; Iadarola, Barbara; Zago, Elisa; Ruperti, Benedetto; Spinelli, Francesco; Zanella, Angelo; Velasco, Riccardo; Ferrarini, Alberto; Chitarrini, Giulia; et al.
Summary: Fruits stored at low temperature can exhibit different types of chilling injury. In apple, one of the most serious physiological disorders is superficial scald, which is characterized by discoloration and brown necrotic patches on the fruit exocarp. Although this phenomenon is widely ascribed to the oxidation of α‐farnesene, its physiology is not yet fully understood. To elucidate the mechanism of superficial scald development and possible means of prevention, we performed an integrated metabolite screen, including an analysis of volatiles, phenols and lipids, together with a large‐scale transcriptome study. We also determined that prevention of superficial scald, through the use of an ethylene action inhibitor, is associated with the triggering of cold acclimation‐related processes. Specifically, the inhibition of ethylene perception stimulated the production of antioxidant compounds to scavenge reactive oxygen species, the synthesis of fatty acids to stabilize plastid and vacuole membranes against cold temperature, and the accumulation of the sorbitol, which can act as a cryoprotectant. The pattern of sorbitol accumulation was consistent with the expression profile of a sorbitol 6‐phosphate dehydrogenase, MdS6PDH, the overexpression of which in transgenic Arabidopsis thaliana plants confirmed its involvement in the cold acclimation and freezing tolerance. Significance Statement: Cold storage can induce severe postharvest disorders in apple, such as superficial scald. Here, comprehensive RNASeq analysis revealed transcriptional re‐programming as a consequence of blocking ethylene receptor level, preventing superficial scald and inducing cold acclimation processes involving phenolic and lipid metabolism. The cryoprotectant role of MdS6PDH, devoted to produce sorbitol, was further validated in transgenic Arabidopsis thaliana .